1996
DOI: 10.1523/jneurosci.16-10-03459.1996
|View full text |Cite
|
Sign up to set email alerts
|

Phasic Firing of Single Neurons in the Rat Nucleus Accumbens Correlated with the Timing of Intravenous Cocaine Self-Administration

Abstract: To examine potential neural mechanisms involved in cocaine self-administration, the activity of single neurons in the nucleus accumbens of rats was recorded during intravenous cocaine self-administration. Lever pressing was reinforced according to a fixed-ratio 1 schedule. On a time base comparable to the interinfusion interval, half the neurons exhibited phasic firing patterns time locked to the cocaine reinforced level press. For almost all neurons, this pattern consisted of a change in firing rate postpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
138
3
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(159 citation statements)
references
References 102 publications
17
138
3
1
Order By: Relevance
“…The long-term cyclic alterations reported here are very similar to those shown previously (Peoples and West, 1996). It has been proposed that these long-term discharges may function to translate declining drug levels to increased motivation for the drug and thereby result in increased drug-seeking behavior (Peoples and West, 1996).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The long-term cyclic alterations reported here are very similar to those shown previously (Peoples and West, 1996). It has been proposed that these long-term discharges may function to translate declining drug levels to increased motivation for the drug and thereby result in increased drug-seeking behavior (Peoples and West, 1996).…”
Section: Discussionsupporting
confidence: 84%
“…Prior studies have shown that these types of rapid discharges reflect the encoding of associative aspects of the self-administration task (Carelli et al, 1993;Carelli, 2002;Chang et al, 1994;Peoples and West, 1996;Uzwiak et al, 1997). For example, Acb neurons that discharge within seconds before the reinforced response for cocaine appear to encode 'anticipation' of impending drug reward (Carelli et al, 1993;Carelli, 2002;.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations